The Monster and the Machine: Degeneration and Technology in H.G. Well's The Time Machine, Bram Stoker's Dracula, and Joseph Conrad's The Secret Agent - Palombo, Nicholas George (My University, 2015)
This thesis argues that the otherwise polarized criticism of degeneration literature of the fin de siècle is reconciled by observing a shift in degeneration as scientific theory to social phenomenon. This shift is prominent in three texts published at the turn of the nineteenth century: H.G. Wells’s The Time Machine (1895), Bram Stoker’s Dracula (1897), and Joseph Conrad’s The Secret Agent (1907). Max Nordau, a cultural critic during the eighteenth century, expressed anxieties about cultural degeneration in Europe. Nordau argued that cross-dressing created an immoral and sexual ambiguity. Moreover, Nordau locates degeneration in the rising decadence of art and culture and fears that Europe is in decline. Moreover, declining birthrates, rising notions of positive eugenics, and middle class perceptions of the lower classes and aristocracy as the degenerate classes tease out the implications of imperialism, hybridity, masculinity, and technology and their contributions to the rising milieu of degeneration during the fin de siècle in England. This thesis explores Nordau’s sense of degeneration through a post-imperial lens and with an eye on Thomas Carlyle’s binary of the dynamic and mechanical cultural poles. It also draws connections between the decline of masculinity, hybridizing identities, mechanical degeneration, and the reliance upon technology in these texts— technologies used to combat scientific and cultural degenerations.
CHAPTER I: Introduction | CHAPTER II: The Machine of Progress and the Victorian Man: Imperialism, Technology, and Masculinity in H.G. Wells's The Time Machine | CHAPTER III: 'The Blood is the Life': Resisting Degeneration and Defeating the (Re)Imperializing Other in Bram Stoker's Dracula | CHAPTER IV: The Fall of the Family: Heteronormativity and the Endless Narrative of Lower Class Degeneration in Joseph Conrad's The Secret Agent
Keywords: Degeneration; Technology; Imperialism; Hybridity; Masculinity; Fin de Siecle